Family and non-family business behaviour in the wine sector: A comparative study. - Soler-García, Ismael Pablo; Gemar-Castillo, Germán; Guerrero-Murillo, Rafael (Elsevier, 2017)
The purpose of this study is to explore the main differences in key variables of winemaking companies in view of their consideration as a family business in Spain. Using a database of 520 wineries with the main variables used in the literature, this paper analyses the differences between being a family or a non-family winery on the performance, size and structure of debt. The companies were classified as family or non-family then a means test was performed for all key variables between both groups. This study suggests that there are significant differences between family and non-family businesses in the return on assets (ROA) and in the operating margin, which are higher in the case of companies classified as family businesses and in the relative debt and debt ratio, which are higher in companies considered to be non-family. The remaining variables are statistically equal. Better margins in family companies could be due to advantages in the prices derived from the products or brands offered or lower agency costs that may lead to an improvement in management costs, which explains such differences. In addition, the lower risk exposure that would lead family businesses to opt for less risky leverage formulas that would lead to increased long-term financing could explain why these advantages are not reflected in the return on equity (ROE).

El propósito de este estudio es explorar las principales diferencias en las variables clave de las empresas vitivinícolas en vista de su consideración como una empresa familiar en España. Utilizando una base de datos de 520 bodegas con las principales variables utilizadas en la literatura, este trabajo analiza las diferencias entre ser una bodega familiar o no familiar sobre el desempeño, el tamaño y la estructura de la deuda. Las empresas fueron clasificadas como familiares o no familiares, para posteriormente realizar un test de medias para todas las variables clave entre ambos grupos. Este estudio sugiere que existen diferencias significativas entre las empresas familiares y las no familiares en la rentabilidad económica (ROA) y en el margen de beneficios, que son mayores en el caso de empresas clasificadas como empresas familiares y en la relación de deuda y deuda relativa, los cuales son más altas en compañías consideradas no familiares. Las variables restantes son estadísticamente iguales. Los mejores márgenes en las empresas familiares podrían deberse a las ventajas en los precios derivados de los productos o marcas ofrecidas o a los menores costes de agencia que pueden conducir a una mejora en los costes de gestión, lo que explica tales diferencias. Además, la menor exposición al riesgo que llevaría a las empresas familiares a optar por fórmulas de apalancamiento menos riesgosas que conducirían a un aumento de la financiación a largo plazo podría explicar por qué estas ventajas no se reflejan en la rentabilidad financiera (ROE).
Comportamiento de las empresas familiares y no familiares en el sector vitivinícola: un estudio comparativo.
Keywords: Vino - Industria; Empresas - Gestión; Beneficios; Family firms; Wine sector; Profitability; Levene’s test; Compare means; Empresas familiares; Sector vitivinícola; Rentabilidad; Prueba de Levene; Comparación de medias